Stevens' Handbook of Experimental Psychology and Cognitive Neuroscience 2018
DOI: 10.1002/9781119170174.epcn204
|View full text |Cite
|
Sign up to set email alerts
|

Olfaction

Abstract: To detect and organize trillions of possible volatile molecules, the human olfactory system deploys approximately 3% of the genes in the human genome as olfactory receptors. Our understanding of how the olfactory system organizes the resulting information has many gaps, and relative to other sensory systems, our current ability to measure and reproduce smells is poor. Here we cover the anatomy, circuitry, and psychophysics of olfaction, with an emphasis on the gaps that prevent us from measuring an odor, repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 224 publications
3
10
0
1
Order By: Relevance
“…Although a systematic analysis of the factor loadings is challenging due to the large number of descriptors, some associations and trends were explored, especially to check if previous results can be replicated. Similar to previous studies (e.g., see [ 2 , 3 , 8 ]), the first component showed a clear association with molecular weight (as shown by the shade of blue in Figure 2 ) and complexity (high loadings of graph vertex complexity index and graph distance complexity index ; both descriptors from alvaDesc). Further exploration showed that the second principal component shows high loadings of descriptors related to descriptors with some relation to polarity or negativity, such as the eta average electronegativity measure , mean atomic Sanderson electronegativity or topological surface area (alvaDesc descriptors).…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…Although a systematic analysis of the factor loadings is challenging due to the large number of descriptors, some associations and trends were explored, especially to check if previous results can be replicated. Similar to previous studies (e.g., see [ 2 , 3 , 8 ]), the first component showed a clear association with molecular weight (as shown by the shade of blue in Figure 2 ) and complexity (high loadings of graph vertex complexity index and graph distance complexity index ; both descriptors from alvaDesc). Further exploration showed that the second principal component shows high loadings of descriptors related to descriptors with some relation to polarity or negativity, such as the eta average electronegativity measure , mean atomic Sanderson electronegativity or topological surface area (alvaDesc descriptors).…”
Section: Resultssupporting
confidence: 88%
“…There are some well-known relations between structure and odor perception. In order to be perceived as odorous at all, a molecule must be volatile enough to evaporate and have specific solubility characteristics to pass through the (hydrophilic) nasal mucosa and bind to the (hydrophobic) olfactory receptors in the olfactory epithelium [ 2 ]. In addition, some functional groups have been associated with characteristics of odor quality.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations